2019
DOI: 10.1002/ecm.1392
|View full text |Cite
|
Sign up to set email alerts
|

The ecology and evolution of seed predation by Darwin's finches on Tribulus cistoides on the Galápagos Islands

Abstract: Predator-prey interactions play a key role in the evolution of species traits through antagonistic coevolutionary arms races. The evolution of beak morphology in the Darwin's finches in response to competition for seed resources is a classic example of evolution by natural selection. The seeds of Tribulus cistoides are an important food source for the largest ground finch species (Geospiza fortis, G. magnirostris, and G. conirostris) in dry months, and the hard spiny morphology of the fruits is a potent agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 67 publications
(116 reference statements)
5
36
2
Order By: Relevance
“…The different functions of upper and lower spines are likely attributed to the fact that upper spines are typically oriented so they are pointing upwards, almost perpendicular to the ground, whereas the lower spines are often shorter and pointing outward in an orientation that likely makes it more difficult for them to adhere to surfaces (Figure , Figure ). These findings suggest that both seed predation and dispersal likely affect adaptive evolution of upper spines, whereas adaptive evolution of lower spines is solely affected by seed predators on the Galápagos (Carvajal‐Endara et al, ). It has already been demonstrated that the strength and direction of selection by seed predators varies across islands as a function of the finch community, and in response to variation in annual precipitation (Carvajal‐Endara et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The different functions of upper and lower spines are likely attributed to the fact that upper spines are typically oriented so they are pointing upwards, almost perpendicular to the ground, whereas the lower spines are often shorter and pointing outward in an orientation that likely makes it more difficult for them to adhere to surfaces (Figure , Figure ). These findings suggest that both seed predation and dispersal likely affect adaptive evolution of upper spines, whereas adaptive evolution of lower spines is solely affected by seed predators on the Galápagos (Carvajal‐Endara et al, ). It has already been demonstrated that the strength and direction of selection by seed predators varies across islands as a function of the finch community, and in response to variation in annual precipitation (Carvajal‐Endara et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggest that both seed predation and dispersal likely affect adaptive evolution of upper spines, whereas adaptive evolution of lower spines is solely affected by seed predators on the Galápagos (Carvajal‐Endara et al, ). It has already been demonstrated that the strength and direction of selection by seed predators varies across islands as a function of the finch community, and in response to variation in annual precipitation (Carvajal‐Endara et al, ). We do not know how seed dispersal varies among islands, but given that most islands are uninhabited by humans, and in light of the prominent role of anthropogenic seed dispersal on the Galápagos (see below), it is likely that selection on upper spines imposed by dispersal agents varies tremendously.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations